Committal deniable signatures over elliptic curves - Han, Song; Liu, Wan-Quan (Institute of Electrical and Electronics Engineers (IEEE), 2004)
In this paper, a new denaible signatue scheme- committal deniable signature scheme is proposed. This scheme has been constructed using bilinear pairings over elliptic curves.